Review of the genus Ceratotarsonemus De Leon, 1956 (Acari: Prostigmata: Tarsonemidae), with description of a new species from the Amazon Forest - Rezende, José Marcos; Lofego, Antonio Carlos; Gulbronson, Connor; Bauchan, Gary; Ochoa, Ronald (Zootaxa, 2018)
The genus Ceratotarsonemus De Leon (Acari: Prostigmata: Tarsonemidae) is reviewed here, with the addition of an updated key for the genus. Ceratotarsonemus amazonicus, sp. nov., found in the Brazilian Amazon rainforest, is described. Phase contrast (PC), differential interference contrast (DIC), low temperature scanning electron microscopy (LT-SEM) and confocal microscopy (CLSM) micrographs are provided. Biological and ecological aspects about the role of this species in its ecosystem are also discussed.